Algoritma Kalibrasi untuk Modul Tekanan pada Alat Uji Triaxial Digital - Catur Hilman A.H.B. Baskoro; Jamaludin, Jamaludin; Hendri Maja Saputra (MACHINERY Jurnal Teknologi Terapan, 2022)
The calibration algorithm for the pressure module in the triaxial digital test equipment is discussed in this paper. In the previous version of the pressure module design, pressure transducer calibration is performed by inserting the sample transducer reading values ​​in a constant variabel placed on the flash program which results in a re-download process performed every calibration. So this study aims to improve the deficiencies with the solution of making a program algorithm for the pressure module used in the calibration process with direct interaction with the computer through serial monitor on the usb communication port. The study was conducted in stages and focused on coding and testing by conducting direct tests on the pressure module and making improvements to the design of the evaluation results. The algorithm is made to function properly and the accuracy value of pressure module readings at 0.12 kg / cm2 = 8.33%, 0.24 kg / cm2 = 4.17% and 0.30 kg / cm2 = 0.00%.